Software-Defined Radio Demonstrators: An Example and Future Trends. (25th February 2009) - Farrell, Ronan; Sanchez, Magdalena; Corley, Gerry
Abstract : Software-defined radio requires the combination of software-based signal processing and the enabling hardware components. In this paper, we present an overview of the criteria for such platforms and the current state of development and future trends in this area. This paper will also provide details of a high-performance flexible radio platform called the maynooth adaptable radio system (MARS) that was developed to explore the use of software-defined radio concepts in the provision of infrastructure elements in a telecommunications application, such as mobile phone basestations or multimedia broadcasters.